Investigating hypoxia in aquatic environments: Diverse approaches to addressing a complex phenomenon - Friedrich, J.; Janssen, F.; Aleynik, D.; Bange, H.; Boltacheva, N.; Cagatay, M.; Dale, A.; Etiope, G.; Erdem, Z.; Geraga, M.; Gilli, A.; Gomoiu, M.; et al. (Copernicus GmbH, 2014)
In this paper we provide an overview of new knowledge on oxygen depletion (hypoxia) and related phenomena in aquatic systems resulting from the EU-FP7 project HYPOX ("In situ monitoring of oxygen depletion in hypoxic ecosystems of coastal and open seas, and landlocked water bodies", http://www.hypox.net). In view of the anticipated oxygen loss in aquatic systems due to eutrophication and climate change, HYPOX was set up to improve capacities to monitor hypoxia as well as to understand its causes and consequences. Temporal dynamics and spatial patterns of hypoxia were analyzed in field studies in various aquatic environments, including the Baltic Sea, the Black Sea, Scottish and Scandinavian fjords, Ionian Sea lagoons and embayments, and Swiss lakes. Examples of episodic and rapid (hours) occurrences of hypoxia, as well as seasonal changes in bottom-water oxygenation in stratified systems, are discussed. Geologically driven hypoxia caused by gas seepage is demonstrated. Using novel technologies, temporal and spatial patterns of water-column oxygenation, from basin-scale seasonal patterns to meter-scale sub-micromolar oxygen distributions, were resolved. Existing multidecadal monitoring data were used to demonstrate the imprint of climate change and eutrophication on long-term oxygen distributions. Organic and inorganic proxies were used to extend investigations on past oxygen conditions to centennial and even longer timescales that cannot be resolved by monitoring.The effects of hypoxia on faunal communities and biogeochemical processes were also addressed in the project. An investigation of benthic fauna is presented as an example of hypoxia-devastated benthic communities that slowly recover upon a reduction in eutrophication in a system where naturally occurring hypoxia overlaps with anthropogenic hypoxia. Biogeochemical investigations reveal that oxygen intrusions have a strong effect on the microbially mediated redox cycling of elements. Observations and modeling studies of the sediments demonstrate the effect of seasonally changing oxygen conditions on benthic mineralization pathways and fluxes. Data quality and access are crucial in hypoxia research. Technical issues are therefore also addressed, including the availability of suitable sensor technology to resolve the gradual changes in bottom-water oxygen in marine systems that can be expected as a result of climate change. Using cabled observatories as examples, we show how the benefit of continuous oxygen monitoring can be maximized by adopting proper quality control. Finally, we discuss strategies for state-of-the-art data archiving and dissemination in compliance with global standards, and how ocean observations can contribute to global earth observation attempts.